Find the number of positive integers x which satisfy
⌊ 9 9 x ⌋ = ⌊ 1 0 1 x ⌋ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f l o o r 9 9 x = f l o o r 1 0 1 x x = 9 9 k + r 1 , r 1 < 9 9 = 1 0 1 k + r 2 , r 2 < 1 0 1
2 k + r 2 − r 1 = 0
r 1 = 2 k + r 2 ( 1 )
Since r 1 = 0 implies that x = 0 , we can eliminate this possibility. For each value of r 1 , there are f l o o r 2 r 1 + 1 nonnegative integers k that satisfy (1). Therefore the solution S is: S = i = 1 ∑ 9 8 ( f l o o r 2 i + 1 )
= i = 1 ∑ 9 8 f l o o r 2 i + 9 8
= i = 2 ∑ 9 7 f l o o r 2 i + 9 8
= 2 × i = 1 ∑ 4 8 k + 1 4 7
= 4 8 × 4 9 + 1 4 7
= 2 4 9 9
Would be great if someone could help me make it look cool
Problem Loading...
Note Loading...
Set Loading...
For any nonnegative integer a , we have ⌊ 9 9 x ⌋ = ⌊ 1 0 1 x ⌋ = a provided that 9 9 a ≤ x < 9 9 ( a + 1 ) 1 0 1 a ≤ x < 1 0 1 ( a + 1 ) and these inequalities are only simultaneously possible provided that 1 0 1 a ≤ x < 9 9 ( a + 1 ) Thus we must have 2 a < 9 9 , and hence 0 ≤ a ≤ 4 9 . For any particular value of a , we must have 1 0 1 a ≤ x ≤ 9 9 a + 9 8 , and hence there are ( 9 9 a + 9 8 ) − 1 0 1 a + 1 = 9 9 − 2 a possible values of x associated with it. Thus the total number of nonnegative integers x such that ⌊ 9 9 x ⌋ = ⌊ 1 0 1 x ⌋ is a = 0 ∑ 4 9 ( 9 9 − 2 a ) = 9 9 × 5 0 − 4 9 × 5 0 = 2 5 0 0 Since we are only interested in positive integer solutions, we must discard the case x = 0 , and so it follows that there are 2 4 9 9 positive solutions.